Postmortem and pre-harvest interventions to improve the tenderness and consistency of beef - Scanga, John A., author; Belk, Keith, advisor; Niswender, Gordon, committee member; Smith, Gary C., committee member; Tatum, J. Daryl, committee member (Colorado State University. Libraries, 1999)
Because the per capita consumption of beef continues to decline and consumers are consistently dissatisfied with the tenderness and palatability of beef, mechanisms to improve these attributes are imperative to the sustainability of the beet industry. The objectives of this research were to examine the effects of postmortem beet marination and pre-harvest oral supplementation with 7-dehydrocholestrol (vitamin D3) on cooked beef tenderness. In the first study. 28 USDA Select top sirloin steaks were randomly assigned to a control group (CT) or one of five marination treatments: 1) 150 mM calcium chloride (CA); 2) 10% solution of beef-flavoring/seasoning mixture (FL): 3) CA and FL (CF); 4) 2.5% sodium phosphate and FL (PF); and, 5) tap water (TW). Steaks were marinated in vacuum pouches, aged for 7 days, cooked to 70° C and evaluated by members of a trained sensory panel. Marination with CA. compared to CT or TW, did not affect tenderness ratings, but increased (P < .05) bitter and metallic flavors compared to CT or TW treatments. Use of FL. alone or in conjunction with CA or sodium phosphate, increased (P < .05) tenderness and juiciness ratings and reduced (P < .05) bitterness and metallic flavors compared to CT. CA and TW marinades. The second study included 191 heifers that were assigned (n = 6) to negative controls or supplemented via oral bolus with one of 7 levels of vitamin D3 (1, 2, 3, 4, 5 million IU D3/d. 2 million IU D3/d plus 75 g CaCO3 or 4 million IU D3/d plus 75 g CaCO3) for 2, 4, 6 or 8 days antemortem. Individual feedlot performance, carcass data and total serum Ca2+ concentrations were collected and Wamer-Bratzler Shear (WBS) force was measured at 2, 7, 14 and 21 days postmortem for longissimus steaks (8 steaks/carcass) cooked to 70° or 85° C. Supplementation with vitamin D3 generally decreased daily feed intake (as-fed), and reduced (P < .05) average daily gains, compared with controls during the 8 d supplementation period. Supplementation with 1, 2, 3, 4. or 5 million IU D3/d for at least 2 d increased (P < .05) total blood serum Ca2+ concentrations compared to those for controls, however, supplementation with any level of vitamin D3, for any length of time up to 8 d did not improve (P > .05) WBS force of steaks cooked to 70 or 85° C at 2, 7, 14, or 21 d of postmortem aging compared with controls. Marination of beet in vacuum pouches, was an effective method that improved the tenderness of beet. Oral supplementation of cattle with vitamin D3 (at high or low doses) for 2 to 8 d before harvest increased total blood serum Ca2+ concentration, but did not improve cooked beef tenderness.
Keywords: agriculture; livestock; animal sciences